Suppression of overt gingival inflammation in tobacco smokers – clinical and mechanistic considerations - DA Scott (Journal compilation 2007 Blackwell Munksgaard, 2007)
Gingivitis is a reversible inflammatory disease of the periodontal tissues. Periodontitis, in addition, involves destruction of the supporting structures of teeth.